Strategi Peningkatan Motivasi Kerja Dosen Dalam Layanan Pembelajaran (Studi Kasus di Akademi Komunitas Teknologi Syarifuddin Lumajang) - Herzegovina, Rani Nurul Laili; Said, M. Mas’ud; Musa, Ali Masykur (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Lecturer work motivation is a condition that has the effect of generating, directing and maintaining behavior related to the lecturer's work environment in achieving organizational goals. The aim of this research is to find out strategies for increasing work motivation of lecturers at the Syarifuddin Lumajang Technology Community Academy. This research uses descriptive qualitative research methods. Data collection techniques use interview techniques, observation. Data analysis is divided into three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that. Implementation of strategies to increase lecturers' work motivation is by socializing lecturers' code of ethics, having LPM, socializing rules regarding performance standards, maintaining a balance of reward and punishment. The driving factors for lecturers' work are professionalism, respect, and instilling lecturers' values of struggle. Inhibiting factors are internal factors and external factors such as vision and mission which are not in the same frequency as the foundation's struggles, lecturer relationships and uncomfortable working conditions. The concept of a strategy to increase lecturers' work motivation increases with the indicators being the creation of RPS, teaching materials, the existence of an assessment system. The quality of lecturers can improve the work of lecturers in carrying out the mandate of the tridharma of higher education.